Andean lupin (Lupinus mutabilis Sweet): Processing effects on chemical composition, heat damage, and in vitro protein digestibility - Córdova-Ramos J.S. (2020)
Background and objective: Andean lupin (Lupinus mutabilis Sweet) has health benefits with promising possibilities for food industry. The aim of this research was to determine the effect of processing (water debittering, extrusion, and spray-drying) on chemical composition, heat damage and in vitro protein digestibility in Andean lupin. Findings: The processing treatment modified all the parameters while the genotype showed limited effect. The untreated lupins had high protein and lipid content (47.4 and 16.2 g/100 g dry matter). The extruded products showed higher protein content (55.7 g/100 g) and digestibility (68.1%) than the untreated lupins, along with limited heat damage (8.7 mg furosine/100 g protein). Spray-drying led to the lowest protein content (31.8 g/100 g) and, when maltodextrin was used, the highest heat damage (54.1 ± 20.7 mg furosine/100 g protein; 0.60 mg hydroxymethylfurfural/kg; 0.58 mg glycosylisomaltol/kg), but also to the maximum protein digestibility (72.8%–74.0%). Conclusions: The chemical composition of Andean lupin was improved by the technological treatments (debittering, extrusion, and spray-drying) applied. Processing enhanced nutritional value and digestibility, without inducing relevant heat damage. Significance and novelty: Extrusion and spray-drying improve the in vitro protein digestibility of Andean lupin flour causing limited heat damage. © 2020 Cereals & Grains Association